Menimbang Khazanah Tafsir Fiqhi - Mujib, Ahmad (Justicia Islamica, 2009)
This study aims to examine the treasure trove of fiqh interpretation as an important contribution to the development of Islamic fiqh. Using a qualitative method and a historical-critical approach, this study traces the development of fiqh interpretation through classical to contemporary texts, as well as its role in bridging the understanding of religious texts with the practice of Islamic law. The results of the study show that fiqhi interpretation provides a more contextual framework for the verses relating to fiqh, and enriches the Islamic intellectual tradition in providing legal solutions to contemporary issues. This study emphasizes the importance of fiqhi interpretation in shaping legal foundations that are adaptive and relevant in the midst of changing times.